Pengaruh Work Life Balance, Teamwork, Person Job Fit Terhadap Kinerja Karyawan Generasi Z di Kota Yogyakarta - Mulyani, Reni Siti; Santosa, Awan (CV. Rayyan Dwi Bharata, 2024)
This research aims to analyze the influence of Work Life Balance, Teamwork, and Person Job Fit on the performance of Generation Z employees in Yogyakarta City. Generation Z, who are familiar with digital technology and were born between 1997 and 2012. This study uses a quantitative approach with survey methods and data collection techniques through questionnaires to collect data from respondents who are Generation Z employees in Yogyakarta. The instrument test results stated that the data in this study was proven to be valid and reliable. In the classical assumption test, it is stated that the data in this study is normally distributed and produces a regression model that is free from multicollinearity and heteroscedasticity. The research results show that Work Life Balance has a positive and significant effect on employee performance, Teamwork has a positive and significant effect on employee performance, Person Job Fit has a positive and significant effect on employee performance. These results have implications for future researchers to study more deeply the influence of work life balance, teamwork, person job fit on employee performance in different objects to broaden their horizons. The managerial implication of this research is the need for companies to pay attention to work life balance, teamwork, and person job fit to improve the performance of generation Z employees.